Donor‐Acceptor Fluorescent Molecular Rotors Appended with Benzocrown Ethers as Doubly Twisted Intramolecular Charge Transfer Based Ratiometric Acidic pH Sensors. Issue 2 (16th December 2015) - Umar, Shahida; Jha, Ajay Kumar; Goel, Atul
Abstract: A fascinating series of highly fluorescent donor‐acceptor‐appended molecular rotors based on benzocrown ethers has been synthesized. The dimethylamino‐based benzocrown ethers have interesting photophysical properties with good quantum yield and emitted dual fluorescence in polar solvents due to doubly twisted‐intramolecular charge transfer (DT‐ICT) character induced by the dimethylamino group and benzocrown ring. The unique dual fluorescence property of the molecular rotors was explored to develop a ratiometric acidic pH sensor. Abstract : Do the twist : A unique benzocrown‐ether‐based molecular rotor was synthesized, which emitted dual fluorescence due to a doubly twisted intramolecular charge transfer (DT‐ICT) state. The dual fluorescence property of the molecular rotor was explored to develop a ratiometric acidic pH sensor.